Whole-genome assembly and analysis of a medicinal fungus: Inonotus hispidus - Tang, Shaojun; Jin, Lei; Lei, Pin; Shao, Chenxia; Wu, Shenlian; Yang, Yi; He, Yuelin; Ren, Rui; Xu, Jun (Frontiers in Microbiology, 2022)
Inonotus hispidus (I. hispidus) is a medicinal macrofungus that plays a key role in anti-tumor and antioxidant functions. To further understand and enhance the value of I. hispidus, we performed whole-genome sequencing and an analysis of its strain for the first time. I. hispidus was sequenced using the Illumina NovaSeq high-throughput sequencing platform. The genome length was 35,688,031 bp and 30 contigs, with an average length of 1,189,601.03 bp. Moreover, database alignment annotated 402 CAZyme genes and 93 functional genes involved in regulating secondary metabolites in the I. hispidus genome to find the greatest number of genes involved in terpenes in that genome, thus providing a theoretical basis for its medicinal value. Finally, the phylogenetic analysis and comparative genomic analysis of single-copy orthologous protein genes from other fungi in the same family were conducted; it was found that I. hispidus and Sanghuangporus baumii have high homology. Our results can be used to screen candidate genes for the nutritional utilization of I. hispidus and the development of high-yielding and high-quality I. hispidus via genetic means.